Efektivitas Trichoderma, sp. Untuk Pengomposan Tandan Kosong Kelapa Sawit - Toto Suryanto; Muhammad Rifki Alfarez (JURNAL CITRA WIDYA EDUKASI, 2021)
The oil palm empty bunches waste is one of the solid wastes from oil palm plantations that can be processed into compos. The composting process can be assisted by biological agents such as Trichoderma sp. This research aims to determine the effects of Trichoderma sp. on the nutrient content of oil palm empty bunches compost and obtain the best dose of Trichoderma sp. This research was conducted at Laboratory of Biologi and Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi from November 2019 to Maret 2020. The research method used was a one factor completely randomized design with 3 treatments: A0 (control), A1 (100 ml Trichoderma sp.), and A2 (200 ml Trichoderma sp.). Each treatments were 3 replications, and each replications consisted of 3 sample plants so the total unit of experiments were 9 units. Data were analized with analysis of variance with α 5 %, If there is a significant treatment effect, the further analysis using LSD test. The result showed that application of Trichoderma sp. for oil palm empty bunches composting only significant affect on N-total, phosphorus, and potassium. However, it did not significantly affect on C-organik and C/N. The best dose of Trichoderma sp. was A0 (control) from the parameters N-total, phosphorus, and potassium.